Is an average Polish student proficient in solving difficult and new problems? - Biernacki, Marek; Misztal, Andrzej (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2015)
Using selected assignments from admission tests for the Wrocław University of Economics during 1993-2004 and the results of the examinations in mathematics, the authors show the need to implement the teaching of problems. The paper includes the solutions to problems from admission tests with comments regarding the most typical mistakes made by students. Our findings agree with the results of the PISA 2012 results in Creative Problem Solving, where Polish 15-year-old students scored below the median, ranked 27th among 40 countries, in spite of being ranked 8th in mathematics among 34 OECD countries.
Didactics of Mathematics, 2015, Nr 12 (16), s. 11-24
Keywords: admission test and course assignments in mathematics; effectiveness of math education; PISA; Programme for International Student Assessment